JNK signaling mediates acute rejection via activating autophagy of CD8+ T cells after liver transplantation in rats - Wang, Xiaowen; Zhu, Wenfeng; Chen, Haoqi; Li, Xuejiao; Zheng, Wenjie; Zhang, Yuan; Fan, Ning; Chen, Xiaolong; Wang, Genshu (Frontiers in Immunology, 2024)
Background: Acute rejection (AR) after liver transplantation (LT) remains an important factor affecting the prognosis of patients. CD8+ T cells are considered to be important regulatory T lymphocytes involved in AR after LT. Our previous study confirmed that autophagy mediated AR by promoting activation and proliferation of CD8+ T cells. However, the underlying mechanisms regulating autophagy in CD8+ T cells during AR remain unclear. Methods: Human liver biopsy specimens of AR after orthotopic LT were collected to assess the relationship between JNK and CD8+ T cells autophagy. The effect of JNK inhibition on CD8+ T cells autophagy and its role in AR were further examined in rats. Besides, the underlying mechanisms how JNK regulated the autophagy of CD8+ T cells were further explored. Results: The expression of JNK is positive correlated with the autophagy level of CD8+ T cells in AR patients. And similar findings were obtained in rats after LT. Further, JNK inhibitor remarkably inhibited the autophagy of CD8+ T cells in rat LT recipients. In addition, administration of JNK inhibitor significantly attenuated AR injury by promoting the apoptosis and downregulating the function of CD8+ T cells. Mechanistically, JNK may activate the autophagy of CD8+ T cells through upregulating BECN1 by inhibiting the formation of Bcl-2 /BECN1 complex. Conclusion: JNK signaling promoted CD8+ T cells autophagy to mediate AR after LT, providing a theoretical basis for finding new drug targets for the prevention and treatment of AR after LT.